Determinants of developmental outcomes in a very preterm Canadian cohort - Synnes, Anne; Luu, Thuy Mai; Moddemann, Diane; Church, Paige; Lee, David; Vincer, Michael; Ballantyne, Marilyn; Majnemer, Annette; Creighton, Dianne; Yang, Junmin; Sauve, Reginald; Saigal, Saroj; et al. (Archives of disease in childhood. Fetal and neonatal edition, 2017)
ObjectivesIdentify determinants of neurodevelopmental outcome in preterm children.MethodsProspective national cohort study of children born between 2009 and 2011 at <29 weeks gestational age, admitted to one of 28 Canadian neonatal intensive care units and assessed at a Canadian Neonatal Follow-up Network site at 21 months corrected age for cerebral palsy (CP), visual, hearing and developmental status using the Bayley Scales of Infant and Toddler Development-Third Edition (Bayley-III). Stepwise regression analyses evaluated the effect of (1) prenatal and neonatal characteristics, (2) admission severity of illness, (3) major neonatal morbidities, (4) neonatal neuroimaging abnormalities, and (5) site on neurodevelopmental impairment (NDI) (Bayley-III score < 85, any CP, visual or hearing impairment), significant neurodevelopmental impairment (sNDI) (Bayley-III < 70, severe CP, blind or hearing aided and sNDI or death.ResultsOf the 3700 admissions without severe congenital anomalies, 84% survived to discharge and of the 2340 admissions, 46% (IQR site variation 38%–51%) had a NDI, 17% (11%–23%) had a sNDI, 6.4% (3.1%–8.6%) had CP, 2.6% (2.5%–13.3%) had hearing aids or cochlear implants and 1.6% (0%–3.1%) had a bilateral visual impairment. Bayley-III composite scores of <70 for cognitive, language and motor domains were 3.3%, 10.9% and 6.7%, respectively. Gestational age, sex, outborn, illness severity, bronchopulmonary dysplasia, necrotising enterocolitis, late-onset sepsis, retinopathy of prematurity, abnormal neuroimaging and site were significantly associated with NDI or sNDI. Site variation ORs for NDI, sNDI and sNDI/death ranged from 0.3–4.3, 0.04–3.5 and 0.12–1.96, respectively.ConclusionMost preterm survivors are free of sNDI. The risk factors, including site, associated with neurodevelopmental status suggest opportunities for improving outcomes.